The Development of KKNI-Based Curriculum at the Arabic Language Education Programs in Indonesian Higher Education - Muhammad, Ismail; Ariani, Safrina (Jurnal Ilmiah Peuradeun, 2020)
This study aimed to analyze the pattern of Indonesian National Qualifications Framework-based curriculum development carried out by 5 best Arabic Language Department (PBA) of undergraduate programs –accredited A- in Indonesia. The method used was qualitative research covering document analysis, interviews, and observations that were applied, and followed by data reduction, data display, and conclusion. The results showed that generally, the PBA departments had developed their curriculum by referring to the steps and rules in the KKNI standard. However, the determination of the courses was not carried out in-depth by developing learning outcomes and lesson materials independently, but only by referring to the CPL from the National Standards for Higher Education (SNPT) of the Minister of Education and Culture Regulation (MOEC) No. 49 of 2014, as well as by adjusting the CPL and the lesson materials to existing courses. This was because the PBA study program had difficulties in developing CPL independently. The curriculum structure developed by PBA was based on the serial model curriculum structure where the courses were arranged from the easiest in the first semester to the most difficult one last semester.